Amorphous fine-diameter SiC-based fiber from a boron-modified polytitanocarbosilane precursor. Issue 4 (April 2018) - He, Guomei; Zhang, Baojie; Wang, Bowei; Xu, Danni; Li, Siwei; Yu, Zhaoju; Chen, Jiangxi
Abstract: An amorphous SiC-based fiber was successfully prepared by the preceramic polymer route from a boron-modified polytitanocarbosilane. It was found that the addition of titanium and boron had adverse effect on melt-spinning, while the tensile strength of the obtained SiC-based fibers increased with the contents of titanium and boron increasing. It is worth mentioning that the decomposition of SiCO phase and the resultant β-SiC crystallization were retarded by the incorporation of titanium and boron into the SiC-based fiber.